Trend changes of the geomagnetic field at the observatory “Argentine Island”: effect in Sq-variations - O. I. Maksimenko; V. G. Bakhmutov; N.A. Kilifarska; O. Ya. Shenderovska (Ukrainian Antarctic Journal, 2013)
Trends of the geomagnetic Sq-variation daily amplitudes on the observatory "Akademic Vernadsky" were obtained with the weakening of the end of the interval 1958 to 2010. The daily Sq-variation amplitudes have trends with the same magnitude of 0.06 nT / year, but different signs for horizontal. SqH and vertical. SqZ components of the geomagnetic variations that are defined by a decrease of 8.6% and 11.3% increase in. The ionospheric conductivity is increasing on ~ 16 % in 50 years. It was found that the secular variations of the magnetic field gives 10% contribution to the trend SqH-geomagnetic variations in the summer, and the effect of Ap index and СО2 anomalies failed to reveal to obs. AIA with the negative trend of the magnetic field in the last century.